(untitled) (Zoological Records and Reviews, 2024)
The Netherlands supports 18 amphibian species, of which nine (50%) are classified as Threatened under the 2023 Dutch Red List. This study provides the first integrated multi-threat analysis of conservation challenges facing Dutch amphibians, combining occupancy modelling, habitat quality assessment, genetic connectivity analysis, and structured expert elicitation to quantify the relative importance of five stressor categories: habitat loss and fragmentation, water quality degradation, road mortality, disease (Batrachochytrium dendrobatidis, Bd; Ranavirus), and climate change. Field surveys at 187 ponds across 12 provinces between 2021 and 2023 (n = 8,341 individual detections) were combined with 18-locus microsatellite genetic analysis of six focal species (n = 1,284 individuals) to assess population structure and landscape connectivity. Occupancy modelling confirmed that water quality degradation (total nitrogen > 2.1 mg/L) and pond isolation (nearest pond distance > 1.2 km) were the strongest negative predictors of great crested newt (Triturus cristatus) occupancy (beta = -0.74 and -0.58 respectively; AUC = 0.88). Genetic differentiation (FST) between pond populations of common toad (Bufo bufo) was significantly higher in agricultural landscapes (mean FST = 0.18 +- 0.04) than in woodland-connected landscapes (FST = 0.07 +- 0.02; t(28) = 8.14, p < 0.001), confirming functional population fragmentation. Bd prevalence was 24.8% across surveyed sites; Ranavirus prevalence 11.4%. Road mortality removes an estimated 4.2-7.8 million amphibians annually across the Netherlands. Expert elicitation ranked habitat loss/water quality as the highest-priority combined threat, followed by road mortality, disease, and climate change. Priority management interventions and a spatially explicit conservation action plan are proposed under EU Habitats Directive and Dutch Nature Policy Programme obligations.